Combined transcriptome and metabolome analysis reveals the regulatory network of histidine kinase QseC in the two-component system of Glaesserella parasuis - Yan, Xuefeng; Zhou, Yuhong; Liu, Songwei; Gu, Congwei; Xiao, Wudian; Zhao, Mingde; Yu, Zehui; He, Lvqin (Frontiers in Microbiology, 2025)
IntroductionGlaesserella parasuis (G. parasuis) causes agent Glässer’s disease in swine. This study investigated the mechanism of QseC in G. parasuis.MethodsThe study utilized transcriptomic and metabolomic sequencing techniques. The ΔqseC mutant was examined using transmission electron microscopy.ResultsTransmission electron microscopy revealed that ΔqseC mutant exhibited cell wall dissolution and cytoplasmic rarefaction, indicating membrane homeostasis disruption. Metabolomics analysis identified 819 metabolites, with 24/36 showing significant alterations in positive/negative ion modes. KEGG enrichment indicated abnormalities in amino acid synthesis and quorum sensing. Transcriptomic revealed 663 differentially expressed genes (DEGs), including upregulated membrane synthesis genes (plsB and wecA) and downregulated virulence factors (hrpA and pilW). Integrated analysis demonstrated that plsB and wecA formed association networks with methionine and prostaglandin metabolites.DiscussionThese results establish QseC’s global regulatory role in G. parasuis, providing insights for novel control strategies.